ANALYSIS OF INFLUENCE THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT ON LITERACY ABILITY IN ELEMENTARY SCHOOLS - Nafillah Dipa Aeiniq; Iqnatia Alfiansyah (Universitas Majalengka, 2023)
The aim of this research is to determine the factors that cause low reading of letters and improve literacy skills through the application of the Pancasila student profile. This type of research is qualitative. The object of this research is SD Negeri 29 Gresik involving grade 1 students, grade 1 teachers and the principal as research subjects. Data collection techniques include observation, interviews, written tests, and documentation. Based on research findings, low literacy can be caused by two main factors, namely internal factors originating from the students themselves and external factors originating from outside influences. Students have included four of the six elements identified as influential in forming literacy skills. Among them are cultivating noble ethics, embracing global diversity, fostering cooperation, and developing critical thinking skills. However, the other two elements, creativity and independence, only show a limited influence on students' reading abilities. Therefore, it is important to emphasize these two aspects to improve students' reading skills. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor penyebab rendahnya membaca huruf dan meningkatkan kemampuan literasi melalui penerapan profil siswa pancasila. Jenis penelitian ini adalah kualitatif. Objek penelitian ini adalah SD Negeri 29 Gresik dengan melibatkan siswa kelas 1, guru kelas 1, dan kepala sekolah sebagai subjek penelitian. Teknik pengumpulan data meliputi observasi, wawancara, tes tertulis, dan dokumentasi. Berdasarkan temuan penelitian, rendahnya literasi dapat disebabkan oleh dua faktor utama yaitu faktor internal yang berasal dari siswa itu sendiri dan faktor eksternal yang berasal dari pengaruh luar. Siswa telah memasukkan empat dari enam elemen yang diidentifikasi berpengaruh dalam membentuk keterampilan literasi. Diantaranya adalah menumbuhkan etika luhur, merangkul keberagaman global, membina kerja sama, dan mengembangkan kemampuan berpikir kritis. Namun, dua elemen lainnya, kreativitas dan kemandirian, hanya menunjukkan pengaruh yang terbatas terhadap kemampuan membaca siswa. Oleh karena itu, penting untuk menekankan kedua aspek tersebut untuk meningkatkan keterampilan membaca siswa.